Young-onset dementia and the need for specialist care: a national and international perspective. (3rd April 2018) - Carter, J.E.; Oyebode, J.R.; Koopmans, R.T.C.M.
ABSTRACT: Objectives: Receiving a timely and accurate diagnosis and gaining access to age-appropriate support for younger people living with dementia (YPD) remains a challenge both in the UK and internationally because the focus of most dementia services is primarily upon the needs of older people. The political case to improve services for YPD depends upon the establishment of an understanding of the clinical symptoms, an unequivocal evidence base about need and an accurate evaluation of the size of the population affected. This short report assesses the evidence base from international studies regarding service design and delivery. The goal is to raise awareness, advance best practice and galvanise the international community to address the serious underfunding and underprovision of care for this marginalised group. Conclusion: The current evidence suggests that there are universal problems, regardless of continent, with delays to diagnosis and poor understanding of optimum models for service provision and long-term care.